Immigration and the origin of Social Work: a shared history - Lacomba Vázquez, Joan (Cuadernos de Trabajo Social, 2021)
The aim of this article is to link immigration with social work in the United States and Great Britain. The article reviews secondary sources to establish the contribution of the pioneering figures of social work and to show the main contributions of the discipline to research and intervention in the field of immigration. These contributions notably include a body of literature that is generally little-known, as well as a series of institutional experiences that have been interpreted as the historical origins of contemporary social work.
Keywords: United States; Great Britain; immigration; pioneers; social work